2016
DOI: 10.3389/fmats.2016.00008
|View full text |Cite
|
Sign up to set email alerts
|

Ferrimagnetic Tb–Fe Alloy Thin Films: Composition and Thickness Dependence of Magnetic Properties and All-Optical Switching

Abstract: Ferrimagnetic rare earth -transition metal Tb-Fe alloy thin films exhibit a variety of different magnetic properties, which depend strongly on composition and temperature. In this study, first the influence of the film thickness (5-85 nm) on the sample magnetic properties was investigated in a wide composition range between 15 and 38 at.% of Tb. From our results, we find that the compensation point, remanent magnetization, and magnetic anisotropy of the Tb-Fe films depend not only on the composition but also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 65 publications
7
67
0
1
Order By: Relevance
“…1(a). As expected, both layers do not show a compensation temperature for these compositions and stay either Tb or Fe dominant [32,33]. We also determined the uniaxial magnetic anisotropy constant K U of both layers as a function of temperature using the expression…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…1(a). As expected, both layers do not show a compensation temperature for these compositions and stay either Tb or Fe dominant [32,33]. We also determined the uniaxial magnetic anisotropy constant K U of both layers as a function of temperature using the expression…”
Section: Resultsmentioning
confidence: 60%
“…Growth-induced variations in the short range order, resulting in a redistribution of the orientation of the Tb magnetic moments, are responsible for the thickness dependence, as discussed in detail in Ref. [32].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…All-optical writing was demonstrated for ferrimagnetic rare-earth transition metal alloy films GdCoFe or TbCoFe around the compensation temperature of the rare-earth and transition metal moments, Figure 6(a) shows single shot switching with two helicities. 73 It was found that the situation is quite complex, 78,79 and it became evident that the demagnetization (memory loss of the spin system) together with some symmetry-breaking mechanism determines the physics of the all-optical switching. 80 The magnetization is not reversed by a 180 rotation, as in a standard recording media (transverse relaxation).…”
Section: B All-optical Switchingmentioning
confidence: 99%